The United Nations World Water Development Report 2003 - United Nations Educational, Scientific; Cultural Organization (United Nations, 2003)
WWDR1 is targeted to all those involved in the formulation and implementation of water-related policies and investment strategies, as well as to professionals at all levels. Although it offers a broad global picture, it focuses particularly on the situation in developing countries, where the need for better infrastructure and governance is highest. With this report, WWAP is aiming to show where systems are failing, and to provide the information needed for efficient and effective capacity-building throughout the world. This 1st edition of the WWDR laid the foundation for subsequent editions, concentrating essentially on evaluating what progress has been made, and not made, since the Rio Summit and on developing effective assessment methodologies. The Report encompasses a broad range of components, focusing on human stewardship of freshwater, that complex aggregation of policies, legislation, social programmes, economic approaches and management strategies through which we seek to achieve water sustainability.